(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper delves into the reimagined portrayal of female characters from the Great Indian Epics in Kavita Kane’s novels Lanka’s Princess (2017), Sita’s Sister (2014) and Karna’s Wife (2013). Kane shifts the narrative lens from the traditionally glorified male protagonists to the often-marginalized women, offering a fresh, empathetic and richly layered exploration of their inner lives. Focusing on characters like Surpanakha, Urmila and Uruvi, the study examines how Kane transforms these peripheral figures into complex protagonists with distinct voices, aspirations and emotional journeys. Through this re-centering, the paper underscores themes of agency, sacrifice and resilience, challenging the patriarchal constructs that have historically confined women in epic literature. By reclaiming and amplifying these female perspectives, Kane not only revitalizes the epic narratives but also offers a more inclusive and humanized interpretation of ancient texts. This study aims to contribute to the evolving discourse on gender in mythology by re-evaluating the depth, strength and significance of women in the Indian epic tradition.